A porcine model of heart failure with preserved ejection fraction: magnetic resonance imaging and metabolic energetics. (18th December 2019) - Charles, Christopher J.; Lee, Philip; Li, Renee R.; Yeung, Teresa; Ibraham Mazlan, Stephane M.; Tay, Zhi Wei; Abdurrachim, Desiree; Teo, Xing Qi; Wang, Wei‐Hsin; de Kleijn, Dominique P.V.; Cozzone, Patrick J.; Lam, Carolyn S.P.; et al.
Abstract: Aims: A significant proportion of heart failure (HF) patients have HF preserved ejection fraction (HFpEF). The lack of effective treatments for HFpEF remains a critical unmet need. A key obstacle to therapeutic innovation in HFpEF is the paucity of pre‐clinical models. Although several large animal models have been reported, few demonstrate progression to decompensated HF. We have established a model of HFpEF by enhancing a porcine model of progressive left ventricular (LV) pressure overload and characterized HF in this model including advanced cardiometabolic imaging using cardiac magnetic resonance imaging and hyperpolarized carbon‐13 magnetic resonance spectroscopy. Methods and results: Pigs underwent progressive LV pressure overload by means of an inflatable aortic cuff. Pigs developed LV hypertrophy (50% increase in wall thickness, P < 0.001, and two‐fold increase in mass compared to sham control, P < 0.001) with no evidence of LV dilatation but a significant increase in left atrial volume ( P = 0.013). Cardiac magnetic resonance imaging demonstrated T1 modified Look‐Locker inversion recovery values increased in 16/17 segments compared to sham pigs ( P < 0.05– P < 0.001) indicating global ventricular fibrosis. Mean LV end‐diastolic ( P = 0.047) and pulmonary capillary wedge pressures ( P = 0.008) were elevated compared with sham control. One‐third of the pigs demonstrated clinical signs of frank decompensated HF, and mean plasma BNP concentrations were raised compared with sham control ( P = 0.008). Cardiometabolic imaging with hyperpolarized carbon‐13 magnetic resonance spectroscopy agreed with known metabolic changes in the failing heart with a switch from fatty acid towards glucose substrate utilization. Conclusions: Progressive aortic constriction in growing pigs induces significant LV hypertrophy with cardiac fibrosis associated with left atrial dilation, raised filling pressures, and an ability to transition to overt HF with raised BNP without reduction in LVEF. This model replicates many aspects of clinical HFpEF with a predominant background of hypertension and can be used to advance understanding of underlying pathology and for necessary pre‐clinical testing of novel candidate therapies.